Diary in a shelter : stories set in lockdown : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Lei, Haoting (Massey University, 2023)
Since December 2019, the COVID-19 pandemic has ravaged the globe, with lasting effects on most people. This project will document the issues arising in the context of the COVID-19 pandemic that led to the lockdown policy in Xi'an, China, from the end of 2019 to 2022, with a particular focus on the story of a young adult who encounters and experiences the lockdown within an ordinary community in Xi'an. Inspired by graphic novels, Diary in a Shelter uses a sequential art approach to create a set of narrative scenes that explore how the visual medium can be used to represent people's psychological experiences during the lockdown. This practice-based design research is focusing on personal narrative through non-fictional references, drawing thirteen key points summarised from media reports as the basis of the visual stories. This artwork aims to become one part of a printed collection, to resonate with community readers. The illustrated scenes in the project highlight how stories can be used by audiences to gain greater understanding and empathy for those who have experienced the lockdown to varied extents. The outcome provides an outlet to deliver messages and keep the stories of a memorable and emotionally impactful and challenging time.
Some Figures are reused under the NZ Copyright Act 1994 s.42 which provides for the copying of a work for purposes of criticism or review.
Keywords: 330316 Visual communication design (incl. graphic design)